Environmental Determinants of Employee Performance in Air Cargo Logistics: Evidence from Indonesia’s Warehouse Sector - Sabang, Yusmiaty; Wibowo, Untung Lestari Nur; Hariri, Ahmad; Jakfar (Indonesian Scientific Publication, 2024)
Background: The work environment is a critical determinant of employee performance, particularly in air cargo logistics where accuracy, speed, and consistency are essential. Despite the increasing focus on technological and automation strategies, environmental conditions remain relatively underexplored. Objective: This study aims to examine the influence of workplace environmental factors on employee performance in the warehouse division of PT Aerojasa Cargo, Jakarta. Method: A quantitative cross-sectional survey was conducted with 55 respondents selected through stratified random sampling. Data were collected using a structured Likert-scale questionnaire measuring five environmental factors (cleanliness, lighting, air circulation, workspace layout, and team collaboration) and five dimensions of performance (accuracy, timeliness, quality, quantity, and neatness). The data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. Results: The findings reveal that 69.9% of the variance in employee performance is explained by workplace environmental conditions (R² = 0.699; p < 0.01). Cleanliness and team collaboration emerged as the strongest predictors across all performance dimensions, while lighting and workspace layout also showed significant contributions. Conclusion: A conducive work environment plays a pivotal role in enhancing warehouse employee performance. Practical implications include continuous investment in cleanliness programs, ergonomic workspace redesign, and participatory evaluation mechanisms. Future research should adopt multi-site and longitudinal approaches to strengthen generalizability.